Effect of chronic muscle contraction on expression of contractile and metabolic proteins in mouse primary cultured myotubes - Yoshitaka Mita; Miyuki Ito; Mio Yamada; Nobuharu L. Fujii; Yasuko Manabe; Yasuro Furuichi (Japanese Society of Physical Fitness and Sports Medicine, 2022)
Endurance exercise induces skeletal muscle adaptations such as fiber-type switching, mitochondrial biogenesis, angiogenesis, and the enhancement of glucose disposal, all of which ameliorate metabolic dysfunction. Since many factors such as body temperature, pH, osmolality, the secretion patterns of neurotransmitters, and humoral factors, change during exercise, it is not easy to determine precisely how each factor contributes to exercise-induced adaptations. To determine these contributions, there is need for experimental studies using an in vitro muscle culture system focusing on a single added stimulus. In this study, we focused on whether contractile stimulation is itself responsible for inducing skeletal muscle adaptations. We constructed a chronic contraction model in mouse primary myotubes and investigated which type of contractile stimulation could induce muscle fiber switching and/or metabolic adaptations. We tested five sets of contractile stimulus conditions, including tetanus and twitch, for different stimulation periods. Of these, when myotubes were stimulated by 6 V/15 mA electric pulses at 1 Hz (20 ms contraction followed by 980 ms relaxation) for 24 hours, we observed a significant increase in the expression of myosin heavy chain (MyHC) I protein, a marker protein for type I (oxidative) myofiber, and a tendency for MyHC IIa expression to increase, a marker protein for type IIa fiber (the most oxidative myofiber out of the type II isoforms). However, the same conditions did not induce any change in the expression of GLUT4, COX IV, and hexokinase II, proteins related to the transport of glucose and metabolism. These results suggest chronic contractile stimulation does not induce the expression of proteins related to metabolism, but it does regulate the expression patterns of MyHC. This chronic contraction model has the potential to clarify the molecular mechanisms underlying the induction of oxidative myofibers in response to muscle contraction.